Artificial Immune Systems approaches to secure the internet of things: A systematic review of the literature and recommendations for future research. (1st May 2020) - Aldhaheri, Sahar; Alghazzawi, Daniyal; Cheng, Li; Barnawi, Ahmed; Alzahrani, Bandar A.
Abstract: As the Internet of Things (IoT) recently attains tremendous popularity, this promising technology leads to a variety of security challenges. The traditional solutions do not fit the new challenges brought by the IoT ecosystem. Although the development's area of Artificial Immune Systems (AIS) provides an opportunity to improve security issues and create a fertile and exciting environment for further research and experiments, there is not any systematic and comprehensive study about analyzing its importance for IoT environment. Therefore, this work aims to identify, evaluate, and perform a comprehensive study of empirical research on the studies of AIS approaches to secure the IoT environment. The relevant and high-quality studies are addressing using three research questions about the main research motivations, existing solutions, and future gaps and directions. The AIS approaches have been divided into three main categories based on IoT layers, and detailed classifications have also been included based on different parameters. To achieve this aim, the authors use a systematic literature review (SLR) as a powerful method to collect and critically analyze the research papers. Also, the authors discuss the selected studies and their main techniques, as well as their benefits and drawbacks in general. This research process strives to build a knowledge base for AIS solutions under the umbrella of IoT security and suggest directions for future research.